Predictors of nutrition care process and terminology use, applicability and importance within Asia‐Pacific dietitians. Issue 4 (5th September 2018) - O'Sullivan, Therese A.; Lo, Johnny; Vivanti, Angela
Abstract : Aim: Many dietitians are yet to incorporate the Nutrition Care Process and Terminology (NCPT) into practice. The present study investigated factors predicting (i) NCPT use, (ii) perceived importance of NCPT implementation and (iii) perceived NCPT applicability to personal dietetic practice among dietitians in the Asia‐Pacific region. Methods: Dietetic association members from Australia, New Zealand and Singapore were invited to participate in an online survey assessing NCPT implementation, knowledge, and self‐rated familiarity, attitudes, benefits, concerns, barriers, and enablers. Forward stepwise logistic regression used all factors to identify predictive dietetic characteristics for current NCPT use, importance or applicability to practice. Results: A total of 377 dietitians (5%–55% of national dietetic memberships surveyed) completed at least one survey question. In logistic regression models, independent positive predictors of current NCPT users were knowledge ( P = 0.003), confidence to implement ( P = 0.036), confidence to write nutrition diagnoses ( P = 0.002) and experiencing managerial support ( P = 0.004). Not seeing a reason to change was a significant negative predictor of NCPT use ( P = 0.003). An independent positive predictor of dietitians viewing NCPT implementation as important was feeling that it will improve patient care ( P < 0.001), while negative predictors were seeing minimal benefit in changing ( P < 0.001) and a preference to continue with current routine ( P = 0.015). Independent positive predictors of dietitians viewing NCPT as applicable to their practice were NCPT knowledge ( P = 0.009), seeing the value of NCPT ( P < 0.001) and attendance at workshops or conferences ( P = 0.014). Conclusions: NCPT implementation may be enhanced thorough activities building confidence, gaining managerial corroboration and demonstration of NCPT benefits, including improved patient care.